Self-reported and agency-notified child sexual abuse in a population-based birth cohort - Mills, R.; Kisely, S.; Alati, Rosa; Strathearn, L.; Najman, J. (2016)
© 2015 Elsevier Ltd. Child sexual abuse (CSA) has been associated with many adverse psychiatric outcomes. However, most studies have relied on retrospective self-report of exposure to CSA. We set out to investigate the incidence of CSA in the same birth cohort using both retrospective self-report and prospective government agency notification, and examine the psychological outcomes in young adulthood. The primary outcomes were measures of DSM-IV diagnoses (CIDI-Auto) at age 21. The 21-year retrospective CSA questions were completed by 3739 participants. CSA was self-reported by 19.3% of males and 30.6% of females. After adjustment for potential confounders, both self-reported and agency-notified CSA were associated with increased odds of lifetime major depressive disorder (MDD), anxiety disorders, and posttraumatic stress disorder (PTSD). For the first time in a birth cohort, this study has shown the disparity between the incidence of CSA when measured by self-report and government agency notification. Despite this discrepancy, adverse psychiatric outcomes are seen when CSA is defined using either method.